Uttalslexikon för talsyntes - Törnqvist, Lars (Nordiske Studier i Leksikografi, 2006)
Pronunciation dictionaries for speech synthesis. The Swedish Library of Talking Books and Braille (TPB) is producing talking books for university students by speech synthesis. To enhance the pronunciation, TPB has started compiling a large electronic pronunciation dictionary. In the initial phase, existing printed dictionaries are imported to the lexical database. As these dic-tionaries were made for human reading, they are transformed to meet the quite different require-ments from the speech synthesis systems.